Perbandingan Metode Dempster Shafer, Case-Based Reasoning dan Certainty Factor dalam Diagnosis Penyakit Craniopharyngioma - Agus Iskandar (Journal of Information System Research (JOSH), 2023)
Craniopharyngioma is a rare benign brain tumor that originates from embryonic tissue of the pituitary gland. It is a type of brain tumor that develops near the pituitary gland at the base of the skull. Its prevalence is approximately 2-4% of all brain tumor cases. Collaboration among the medical team is crucial in providing optimal perioperative care. In diagnosing craniopharyngioma, an expert system can be utilized. The Expert System aids in identifying problems and providing appropriate solutions. Its existence can expedite the process of problem identification and system repair. Additionally, the Expert System can also help reduce consultation costs with experts, as it can provide solutions comparable to those given by experts. This study aims to compare the results of the Dempster-Shafer, Case-Based Reasoning, and Certainty Factor methods in diagnosing craniopharyngioma. The study will determine the percentage results of the Dempster-Shafer, Case-Based Reasoning, and Certainty Factor methods in diagnosing craniopharyngioma to ascertain which method is most accurate in diagnosing the disease. The percentage results from the application of the DS and CF methods yielded the same result of 99.8%, whereas the CBR method only achieved a diagnosis percentage of 51.4% for craniopharyngioma. Hence, it can be observed that the CBR method yields the lowest percentage diagnosis for craniopharyngioma.